Operational Tolerance in Xenotransplantation By Use of Regulatory T Cells with a SLA-specific Chimeric Antigen Receptor. (July 2018) - Zimmermann, Katharina; Noyan, Fatih; Hust, Michael; Schwinzer, Reinhard; Hundrieser, Joachim; Hardtke-Wolenski, Matthias; Tenspolde, Michel; Petersen, Bjoern; Niemann, Heiner; Huehn, Jochen; Geffers, Robert; Manns, Michael; et al.
Abstract : Organ shortage is currently the biggest hurdle in the successful treatment of patients with organ failure. Xenotransplantation, using porcine cells, tissues and organs may be one of the ways to avoid the growing organ shortage. Clinical translation is currently limited by strong xenospecific immune responses requiring intense immunosuppression. CD4+CD25highFOXP3+ regulatory T cells (Tregs) are involved in graft-specific tolerance after solid organ transplantation and in xenotransplantation. However, adoptive transfer of polyspecific Tregs alone is insufficient to prevent graft rejection even in rodent models, indicating that graft-specific Tregs are required. Methods: SLA-specific scFvs were generated by antibody-phage display panning using an swine leucocyte monomer. These were used to generate a highly specific chimeric antigen receptor that specifically recognizes SLA (referred to as X-CAR). Results: Transduction into nTregs changed the specificity of the nTregs without alteration of their regulatory phenotype and epigenetic stability. Specificity studies using NFAT-GFP hybridoma cells revealed exclusive specificity against porcine target structures. Any cross-reactivity with human cells or self-activation could be ruled out. Xenospecific-mixed lymphocyte reactions were efficiently suppressed by X-CAR nTregs. Most importantly, X-CAR Tregs completely prevented rejection of allogeneic target cells and tissues in immune reconstituted humanized mice in the absence of any immunosuppression (operational tolerance). Conclusion: X-CAR Tregs can induce xeno-specific tolerance without perturbation of the general immune competence of the recipient. Therefore, these modified cells have great potential for incorporation into clinical trials using porcine tissues or grafts.